Web-flange behavior of pultruded GFRP I-beams: A lattice model for the interpretation of experimental results. (1st September 2016) - Fascetti, Alessandro; Feo, Luciano; Nisticò, Nicola; Penna, Rosa
Abstract: Glass fiber reinforced polymer (GFRP) I-beams have seen growing interest in the last decades, so that they are now being used in many civil applications. For this reason various experimental campaigns have been performed to study the structural response of such elements. In particular, experimental tests performed by Feo et al. [1] highlighted the need to study the local problem of the web-flange junction when pultruded I-beams are subjected to loads acting in the web plane: the experimental results dispersion stimulated numerical analyses and the need to study the problem by means of a nonlinear mesoscale lattice model approach that helped in the experimental result interpretation. The lattice model proposed has several appealing features that make it suitable for the simulation of orthotropic materials like GFRP. The different steps needed to build the model, and the constitutive law used will be explained and the achieved main results will be given in order to conclude that fluctuations in the effective contact area and local material non linearity can be the reasons for the measured dispersion for both element stiffness end strength.